Efektivitas Kepemimpinan Kepala Sekolah Kristen di Masa Pandemi Covid-19 - Nasib Tua Lumban Gaol; Tresia Ronestyka Sitinjak; Johanes Waldes Hasugian (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2021)
Every Christian principal has many tasks and responsibilities in managing school which are very tricky because the educational organization needs to operate effectively and efficiently. As a Christian leader, the principal must carry out appropriately the practice of leadership in a time of the Covid-19 pandemic. The Christian principals must conduct effective leadership in order to drive, motivate, and direct all people at the school for attaining the aims of education. This article is to investigate factors contributing to the effectiveness of Christian principal leadership that a literature review was used. The result of the study identified four factors that promote the effectiveness of Christian principal leadership, namely a good relationship with God; having the right attitude, vision, and mission of the school based on Christian values; and the availability of school resources. This study also contributes toward the improvement of the knowledge about Christian school principals. Moreover, researchers and practitioners in Christian education are strongly recommended to explore further the topic of Christian principal leadership for the improvement of Christian school management.